Implementation of A Role-Playing Central Learning Model in the Formation of Children's Character at the Age of 4-5 Years - Wahyuni, Ayu; Musayyadah (PROGRAM STUDI MAGISTER PENDIDIKAN ISLAM ANAK USIA DINI (PIAUD) FAKULTAS ILMU TARBIYAH DAN KEGURUAN UIN SUNAN KALIJAGA YOGYAKARTA, 2024)
The role play center model provides a stimulating environment for children to learn through play. In this research, the children observed were students at the Al-Azhar Kowel Pamekasan Kindergarten. This research aims to describe the process of implementing the role-playing center learning model as an effort to shape character, moral values to strengthen children's character. Knowing the results of implementing the role-playing center learning model in forming children's character and describing the supporting and inhibiting factors for implementing the learning model in character-building in play groups. This research uses descriptive qualitative methods. With data collection methods using observation, interviews and documentation. The interview subjects in this research were three or two teachers who were interviewed by the researcher . Based on the consideration that the implementation of the role-playing learning model in character formation involves various aspects which must be explored in depth and comprehensively in this research. The results of the research show that the implementation of the role-playing center learning model in character building play groups at PAUD Al-Azhar Kowel Pamekasan begins with 1) The teacher gathers the children first, 2) The teacher explains the rules of play to the children, 3) explains the theme and sub-theme of role playing with children, 4) dividing roles among children according to the topic, 5) children can carry out role playing activities, 6) the teacher supervises children when role playing activities are carried out. Keywords : central learning, character formation, early childhood